Effects of oestrogen deficiency and 17 beta-estradiol therapy on bone healing in calvarial critical size defects treated with bovine bone graft - Almeida, Juliano Milanezi de [UNESP]; Bosco, Alvaro Francisco [UNESP]; Faleiros, Paula Lazilha [UNESP]; Cabrera Pazmiño, Victor Fabrizio [UNESP]; Murakawa, Ana Cristina [UNESP]; Bonfante, Samara [UNESP]; Nagata, Maria José Hitomi [UNESP]; Garcia, Valdir Gouveia [UNESP] (Elsevier B.V., 2015)
Objective: To histomorphometrically analyze the effect of ovariectomy-induced oestrogen deficiency and 17 beta-estradiol therapy on bone healing of surgically created critical-size defects (CSDs) treated with bovine bone graft (BBG).Methods: Forty-eight female rats were randomly assigned to the following 3 experimental groups (n = 16): sham-operated animals (SHAM), ovariectomized animals (OVX) and ovariectomized animals treated with oestrogen (OVX+E2). OVX+E2 animals received daily subcutaneous injections of 17 beta-estradiol (20 mu g/kg) from 8 days after ovariectomy until euthanasia. Thirty days after the surgery, an 8 mm CSD was surgically created in each calvaria of all animals and filled with BBG. Animals were euthanized at either 30 or 60 days postoperative. A histological analysis, percentage of Newly Formed Bone Area (NFBA), osteoblast and osteoclast number was histomorphometrically performed (p <= 0.05).Results: At 30 days, SHAM group (8.82% +/- 2.93) had significantly greater NFBA than OVX (4.66% +/- 1.35) and OVX+E2 groups (5.85% +/- 4.08) (p <= 0.05). At 60 days, SHAM group (11.51% +/- 3.08) and OVX+E2 group (9.84% +/- 1.87) had significantly greater NFBA than OVX animals (5.12% +/- 0.68) (p <= 0.05). Fewer osteoblasts were observed in the OVX group at 30 (763.40 +/- 121.60) and 60 (696.60 +/- 80.92) days than in the SHAM group at 30 days (1356.00 +/- 95.38). Fewer osteoclasts were observed in the OVX+E2 group (3.25 +/- 2.16) than in the SHAM (9.75 +/- 1.82) and OVX (12.75 +/- 1.47) groups at 30 days (p <= 0.05).Conclusions: Oestrogen deficiency compromises bone healing in calvarial CSDs treated with BBG in ovariectomized rats. After 60 days post-surgery, 17 beta-estradiol therapy improved bone healing in calvarial CSDs treated with BBG in ovariectomized rats.
Keywords: Bone grafting; Bone regeneration; Oestrogen replacement therapy; Calvaria